"A Blessing and a Curse" Couples Dealing with Ambivalence Concerning Grandparental Involvement During the Transition to Parenthood—A Longitudinal Study. (May 2021) - Zartler, Ulrike; Schmidt, Eva-Maria; Schadler, Cornelia; Rieder, Irene; Richter, Rudolf
This contribution provides an investigation of first-time parents' experiences and strategies in dealing with ambivalence—i.e., the simultaneous presence of contradictory emotions—regarding grandparental involvement during the transition to parenthood. The study is based on qualitative longitudinal case studies comprising in-depth individual interviews with 11 Austrian couples of first-time mothers and fathers prebirth, and six months and two years after childbirth ( n = 66 interviews). Parents reported ambivalent feelings toward grandparental involvement during all stages of the transition process. We identified three parental strategies for dealing with ambivalence: inclusion, delimitation, and exclusion. Intracouple dynamics are shown to be the key aspect in the variation of these strategies over time. These dynamics are captured in three longitudinal patterns: parallel, divergent, and convergent paths. Overall, the study points to the complexity and fluidity of intergenerational relationships and demonstrates the challenges of negotiating ambivalence within couples and families during the transition to first-time parenthood.